ESCOLHA ADEQUADA DOS TESTES ESTATÃSTICOS PARA COMPARAÇÃ•ES MÚLTIPLAS - Conagin, Armando; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
ESCOLHA ADEQUADA DOS TESTES ESTATÃSTICOS PARA COMPARAÇÃ•ES MÚLTIPLAS